Thalamic altered spontaneous activity and connectivity in obstructive sleep apnea syndrome. Issue 2 (28th December 2021) - Santarnecchi, Emiliano; Sprugnoli, Giulia; Sicilia, Isabella; Dukart, Juergen; Neri, Francesco; Romanella, Sara M.; Cerase, Alfonso; Vatti, Giampaolo; Rocchi, Raffaele; Rossi, Alessandro
ABSTRACT: Background and Purpose: Obstructive sleep apnea (OSA) syndrome is a sleep disorder characterized by excessive snoring, repetitive apneas, and nocturnal arousals, that leads to fragmented sleep and intermittent nocturnal hypoxemia. Morphometric and functional brain alterations in cortical and subcortical structures have been documented in these patients via magnetic resonance imaging (MRI), even if correlational data between the alterations in the brain and cognitive and clinical indexes are still not reported. Methods: We examined the impact of OSA on brain spontaneous activity by measuring the fractional amplitude of low‐frequency fluctuations (fALFF) in resting‐state functional MRI data of 20 drug‐naïve patients with OSA syndrome and 20 healthy controls matched for age, gender, and body mass index. Results: Patients showed a pattern of significantly abnormal subcortical functional activity as compared to controls, with increased activity selectively involving the thalami, specifically their intrinsic nuclei connected to somatosensory and motor‐premotor cortical regions. Using these nuclei as seed regions, the subsequent functional connectivity analysis highlighted an increase in patients' thalamocortical connectivity at rest. Additionally, the correlation between fALFF and polysomnographic data revealed a possible link between OSA severity and fALFF of regions belonging to the central autonomic network. Conclusions: Our results suggest a hyperactivation in thalamic diurnal activity in patients with OSA syndrome, which we interpret as a possible consequence of increased thalamocortical circuitry activation during nighttime due to repeated arousals.